Mass Spectrometry Reveals New Insights into the Production of Superoxide Anions and 4‐Hydroxynonenal Adducted Proteins in Human Sperm. Issue 2 (9th January 2020) - Netherton, Jacob Kendal; Hetherington, Louise; Ogle, Rachel Anne; Gavgani, Marum Mazloumi; Velkov, Tony; Villaverde, Ana Izabel Bilbin; Tanphaichitr, Nuch; Baker, Mark Andrew
Abstract: The free‐radical theory of male infertility suggests that reactive oxygen species produced by the spermatozoa themselves are a leading cause of sperm dysfunction, including loss of sperm motility. However, the field is overshadowed on several fronts, primarily because: i) the probes used to measure reactive oxygen species (ROS) are imprecise; and ii) many reports suggesting that oxygen radicals are detrimental to sperm function add an exogenous source of ROS. Herein, a more reliable approach to measure superoxide anion production by human spermatozoa based on MS analysis is used. Furthermore, the formation of the lipid‐peroxidation product 4‐hydroxynonenal (4‐HNE) during in vitro incubation using proteomics is also investigated. The data demonstrate that neither superoxide anion nor other free radicals that cause 4‐HNE production are related to the loss of sperm motility during incubation. Interestingly, it appears that many of the 4‐HNE adducted proteins, found within spermatozoa, originate from the prostate. A quantitative SWATH analysis demonstrate that these proteins transiently bind to sperm and are then shed during in vitro incubation. These proteomics‐based findings propose a revised understanding of oxidative stress within the male reproductive tract.